Polemik Pelaksanaan Putusan Pengadilan Tata Usaha Negara - Rokhman, Arief; Pranoto, Edi (PMIH Untag Semarang, 2025)
The State Administrative Court is expected to be able to give a fair and enforceable decision. However, in reality, there are decisions of the State Administrative Court that are not implemented by the parties who are ordered to implement the judge's decision. With the formulation of the problem of how to implement the execution of the decision of the Palembang State Administrative Court Number 25/G/2022/PTUN. PLG; and how to sanction defendants who do not implement the Court's decision. This article was prepared using the normative juridical method. conclusion that the execution effort is based on the decision of the Palembang State Administrative Court Number 25/G/2022/PTUN. PLG that is not carried out by the defendant can be done by, then an active role of the Plaintiff is required, because it must submit an application to the court. Meanwhile, sanctions can be given to the Village Head (defendant) who does not implement the decision of the Palembang State Administrative Court Number 25/G/2022/PTUN. PLG is a gradual administrative sanction from written reprimand to dismissal based on the provisions of Law number 6 of 2014 concerning Villages and Law Number 30 of 2014 concerning Government Administration, and the parties involved in the mechanism of sanctioning the defendant Village Head involve the Village Consultative Body, Sub-district Head, District Inspectorate, Village Community Empowerment Office, Regent and Palembang State Administrative Court.